A Preliminary Survey of Color Discrimination Among Indonesia Female Subjects Using Farnsworth-Munsell Hue Color Test - TIUAJ, Yanto; Hizkia Wicaksono, Michael (Prodi Teknik Elektro, Fakultas Teknik Unika Atma Jaya Jakarta, 2022)
This study aimed to conduct a preliminary survey of the color discrimination test among Indonesian samples. The study involved 26 participants of university students and office workers. To test the ability of color discrimination, the Farnsworth-Munsell (FM) 100 Hue Color Vision Test was used. Farnsworth-Munsell test scoring software was also used to obtain the total score of each participant. Using the FM 100-hue test, the participants were classified into superior, average and low color discrimination ability. The results showed that that 19.2% female participants were classified as superior for color discrimination ability. Majority of participants were classified as average. Meanwhile for low classification, only 3.9% were classified as low color discrimination ability. Currently, many companies and industries have great need for workers with good characterized and accurate color vision. However, the study of color discrimination is still limited and unknown in Indonesia. Through this study, hopefully attention for a broader study with a larger scale could be obtained.